Modes of Antigen Presentation by Lymph Node Stromal Cells and Their Immunological Implications - Hirosue, Sachiko; Dubrot, Juan (Frontiers in Immunology, 2015)
Antigen presentation is no longer the exclusive domain of cells of hematopoietic origin. Recent works have demonstrated that lymph node stromal cell (LNSC) populations such as fibroblastic reticular cells, lymphatic and blood endothelial cells not only provide a scaffold for lymphocyte interactions, but also exhibit active immunomodulatory roles that are critical to mounting and resolving effective immune responses. Importantly, LNSCs possess the ability to present antigens and establish antigen-specific interactions with T cells. One example is the expression of peripheral tissue antigens, which are presented on major histocompatibility complex (MHC)-I molecules with tolerogenic consequences on T cells. Additionally, exogenous antigens, including self- and tumor antigens can be processed and expressed on MHC-I complexes, which result in dysfunctional activation of antigen-specific CD8+ T cells. While MHC-I is widely expressed on cells of both hematopoietic and non-hematopoietic origins, antigen presentation via MHC-II is more precisely regulated. Nevertheless, LNSCs are capable of endogenously expressing, or alternatively, acquiring MHC-II molecules. Transfer of antigen between LNSC and dendritic cells in both directions has been recently suggested to promote tolerogenic roles of LNSCs on the CD4+ T cell compartment. Thus, antigen presentation by LNSCs is thought to be a mechanism that promotes the maintenance of peripheral tolerance, as well as generates a pool of diverse, antigen-experienced T cells for protective immunity. This review aims to integrate the current and emerging literature to highlight the importance of LNSCs in immune responses, and emphasize their role in antigen trafficking, retention and presentation.